Analysis of Online Learning During the Covid-19 Period using the Ordinary Least Square (OLS) Method - Matdoan, Muhammad Yahya; Irianto, Wahyu (Pattimura International Journal of Mathematics (PIJMath), 2022)
Education is the main capital to create quality human resources to face the challenges of the times that continue to develop rapidly. At the end of 2019, Indonesia experienced an outbreak of the COVID-19 pandemic. It makes learning activities carried out from home or online. Online learning aims to meet educational standards by utilizing information technology using a computer or mobile devices that are interconnected between students and teachers via an internet connection. However, there are several problems in the online learning process, both among teachers and students, as well as the facilities used in learning. The method of least squares (Ordinary Least Square) is one of the estimation methods used to analyze the relationship between the predictor variable (independent variable) and the response variable (dependent variable). This study aimed to identify and analyze online learning problems during the covid-19 pandemic. The data used in this study were sourced from Public Senior High School 11 Ambon, with the variables used being learning motivation (X1), teacher's role (X2), and student learning outcomes (Y). This study concluded that student learning outcomes in online learning at Public Senior High School 11 Ambon were in a low category, student motivation in learning is in the moderate category, and the role of the teacher is in the moderate category. In addition, the variables of learning motivation and the role of the teacher together have a positive effect on student learning outcomes. The amount of the contribution of the influence of learning motivation and the role of the teacher to student learning outcomes at Public Senior High School 11 Ambon is 61.9%, while other factors outside the study influence the remaining 38.1%.